IZIN POLIGAMI DARI ISTRI DI PENGADILAN DALAM PERSPEKTIF MASHLAHAH MURSALAH - Zulfan Efendi (PERADA, 2018)
This article would like to see the rule of law related the need of consent from a wife for her husband who will do polygamy from the perspective of mashlaha mursalah. One of the requirements in a court session is the need for the court to obtain a consent statement from the wife and need to check and confirm the wife’s consent. In this study, it was concluded that the consent of the wife conveyed before the trial is a fundamental need (mashlahah hajiyah) to protect the absolute need (mashlahah daruriyah) in the form of happiness in the household. Based on related studies focusing on the impact, most wives did not sincerely give their consent for polygamy. Therefore, the court must invite the wife to obtain direct information on the consent of polygamy given to her husband.